Blue moon promise [large type] - Coble, Colleen (Coble, Colleen. Under Texas stars, 2012)
Lucy Marsh's worldly resources are running out, but she's fiercely determined to care for her younger brother and sister. When she discovers that their father's recent death was no accident, Lucy is eager to leave town. She accepts a proxy marriage she believes will provide safe refuge. But trouble follows her to Texas where her new husband is surprised to suddenly have a wife and children to care for. Nate Stanton always hoped he'd marry someday, but running the family ranch meant he had no time for romance. When his father deposits Lucy Marsh--a city girl--on his doorstep, with two siblings in the bargain, he expects ranch life will send her running on the first train out of town. But Lucy is made of tougher stuff than Nate imagined. When danger moves in, Nate finds he'd give anything to protect Lucy and the children he's grown to love. Even if it means giving up his ranch.